Proceedings from the 2018 Association for Chemoreception Annual Meeting Symposium: Bariatric Surgery and Its Effects on Taste and Food Selection - Spector, Alan C (Chem Senses, 2019)
This article provides a summary of the topics discussed at the symposium titled “Bariatric Surgery and Its Effects on Taste and Food Selection,” which was held at the Fortieth Annual Meeting of the Association for Chemoreception Sciences. Bariatric surgery such as Roux-en-Y gastric bypass (RYGB) is currently one of the most effective treatments available for weight loss and Type 2 diabetes. For this reason, it is of great interest to clinicians as well as to basic scientists studying the controls of feeding and energy balance. Despite the commonly held view by clinicians that RYGB patients change their food preferences away from fats and sugars in favor of less energy dense alternatives such as vegetables, the empirical support for this claim is equivocal. It is currently thought that the taste and palatability of fats and sugars are affected by the surgery. Some key preclinical and clinical findings addressing these issues were evaluated in this symposium.